Deteksi Antibodi Serum Terhadap Virus Avian influenza pada Ayam Buras - Darmawi Darmawi; Zakiyah Heryawati Manaf; Darniati Darniati; Fakhrurrazi Fakhrurrazi; Mahdi Abrar; Erina Erina (Jurnal Agripet, 2012)
Detection on Serum Antibodies of Native Chickens to Avian influenza VirusABSTRACT. An important approach of controlling against Avian Influenza should be determined to detect the antibody titres of bird flu caused by Influenza virus H5N1 in Indonesia. The aim of the present study was to detect the antibodies to Avian Influenza in serum of native chickens. This study utilized 123 serum samples collected from the axilaris vein (left or right) of native chickens. Antibody titres were examined using Hemaglutination Inhibition (HI). The result showed that indication of natural infection by Avian Influenza (H5N1) in native chickens, as shown that out of 123 serum samples, 16 (13,01%) were tested positive by HI, while only 10 (8,13%) were tested protective to Avian influenza infection. Based on the results we obtained, a conclusion that natural infection by Avian influenza virus stimulated variety level of formation antibody titres in native chickens.